Effect of Temperature and Time on the Physical Properties of Bread Produced from Wheat – Cocoyam Flour Using Response Surface Methodology - O.A, Peluola-Adeyemi; T.E, Obi; D.I, Ugbogu (Journal of Food Technology Research, 2016)
This study investigated the effect of baking temperature and time on the physical properties of bread from 10% cocoyam and 90% wheat flour. A central composite rotatable experimental design with two factors and five levels were used. The independent factors were baking temperature (174.82 – 251.18oC) and baking time (30 – 45min). The responses were specific loaf volume (Y1), crumb moisture (Y2), crumb hardness (Y3) and overall acceptability (Y4). Thirteen (13) baking trials were performed with five center points and eight non center points. The specific loaf volume (3.35 – 3.9cm3/g), crumb moisture content (32.1 – 35%), crumb hardness (70 – 70.48N) and overall acceptability (4.85 – 8) varied significantly (P<0.05) with the baking temperature and time. The panelists preferred the bread baked at 186oC for 45min.